Aspectos petrográficos e geoquímicos de côndrulos em meteoritos primitivos: um estudo de caso a partir do meteorito Campo Sales - Pereira, Cristine de Almeida (2023)
Chondritic meteorites represent fascinating reminders of the early history of the Solar System evolution, from the beginning of the Nebula to its current configuration. Through the study of the chondrules - small particles present in the chondrite - it is possible to learn how the composition and evolutionary processes that predominated in the first stages of nebular development. This study aimed to better understand these processes, through the mineral chemistry and petrography of the chondrules present in the Campos Sales meteorite. This meteorite shows small chondrules, with maximum dimensions of 1 mm, and a mineralogy predominantly constituted by: olivine (Fa25), enstatite (En77, Fs23), augite (En51, Fs8, Wo41), and plagioclase. Troilite, Fe-Ni metal alloy, chromite and chlorapatite crystals occur as inclusions. In textural terms, three types were classified: barred, radial and granular. The barred and radial chondrules display skeletal crystals of olivine or enstatite, respectively, and diameters of approximately ~0.8. It is verified that the association of plagioclase with augite is recurrent in all types of chondrules, with textures that are like intergrowth. Crystals of chromite, enstatite, and olivine were found in close association with the chondrules of plagioclase. The mineral chemistry allowed to classify this plagioclase as oligoclase (Or6, Ab84, An10), as well as to notice that most crystals of olivine and pyroxene have little core-border compositional variation and were very close to the equilibrium with the liquid during their crystallizations. The processes required to explain the origins of these chondrules evoke different sources areas in the nebula. Later, during the accretionary phase, these particles were combined to form Campos Sales meteorite’s parental body and the groundmass that involves them. In view of the little compositional variation within the crystals and in the absence of glass in the matrix, we propose a thermal event, that devitrified the glass and allowed chondrules’s chemical rebalancing.